2013
DOI: 10.1097/wnp.0b013e3182872f70
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotemporal Ictal Patterns Compared With Mesial and Neocortical Temporal Ictal Patterns

Abstract: Pseudotemporal ictal patterns are morphologically indistinguishable from true temporal ictal patterns. Although statistically more common in hippocampal sclerosis, rhythmic theta pattern can be seen as a result of propagation from extratemporal sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
(23 reference statements)
1
6
0
Order By: Relevance
“…24 In line with this study, the presence of ictal onset as rhythmic theta discharge was more frequently observed in mesial TLE than lateral TLE or TPE. 18,25 The PET scans revealed lateralization value in most of our patients, in concordance to the epileptogenic zone defined by the intracranial monitoring, regardless of the MRI findings. Similarly, it was localized to the seizure onset zone's lobe in 75% of the patients.…”
Section: Facial Contractionsupporting
confidence: 75%
“…24 In line with this study, the presence of ictal onset as rhythmic theta discharge was more frequently observed in mesial TLE than lateral TLE or TPE. 18,25 The PET scans revealed lateralization value in most of our patients, in concordance to the epileptogenic zone defined by the intracranial monitoring, regardless of the MRI findings. Similarly, it was localized to the seizure onset zone's lobe in 75% of the patients.…”
Section: Facial Contractionsupporting
confidence: 75%
“…The reasons for surgery failure are complex and variable, but emerging evidence points to failure to resect epileptogenic areas either within or outside the operated temporal lobe (7,(29)(30)(31). This situation can be defined as a dual pathology combining an extratemporal epileptogenic lesion and temporal epileptogenic zone (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…The caveat guarding against an overreliance on ictal scalp EEG patterns for localization, is that an Ebersole type I pattern can also be seen in pseudotemporal (so called TLE mimics) epilepsy, indicating that this rhythmic theta pattern can be a result of propagation from extratemporal regions . On the other hand, atypical or nonlocalizing scalp EEG findings may very well demonstrate mesial temporal seizure onset on ICEEG, again reiterating the limited reliability of electroclinical localization in TLE.…”
Section: Electrophysiologic Studies: Scalp and Intracranial Eeg (Iceementioning
confidence: 99%